THE BENEFITS OF ABU JAHL (BITTER MELON), ITS ROLE IN MODERN PHARMACEUTICALS AND TRADITIONAL MEDICINE - Bektayeva Khuriyat Ortigaliyevna (Modern American Journals, 2025)
This article analyzes the role of Abu Jahl (bitter melon) in traditional medicine, its beneficial and harmful properties, as well as the information provided about this plant in the works of Ibn Sina, based on scientific sources. The study examines the chemical composition of Abu Jahl melon, its pharmacological effects, and its use in modern medicine. Excerpts from Arabic sources were reliably translated into Uzbek, and the positive and negative effects of the plant on human health are explained. As a result, it is scientifically proven that Abu Jahl melon should be used cautiously in folk medicine, as it possesses both medicinal benefits and toxic effects.
Keywords: Abu Jahl, bitter melon, traditional medicine, Ibn Sina, beneficial properties, harmful effects, medicine.